Preparação de compostos orgânicos aplicados a síntese eletroquímica de polímeros eletroluminescentes - Santos, Fabio Santana dos (2009)
The discussion presented in this master’s degree dissertation resulted in a study about the development of synthesis routes for obtaining the following organic compounds: 4-(decyloxy)-2,5-bis(dibromomethyl)benzonitrile and 2,5-bis(dibromomethyl)-4-(pentyloxy)benzonitrile. The interest in produced such compounds is related to the preparation, by electrochemical route, of poly(p-phenylenevinylene) (PPV) like polymers in which the decyloxy and/or penthyloxy groups act conferring solubility to the polymeric chain and the group cyano acts altering the electronic structure of the polymeric material intendy to produce a electroluminescente polymer with optimized characteristics for the application in light emitting devices. In that way this text describes the preparation and the characterization of a series of organic compounds. The compounds of interest were prepared after realization of a series of synthetic routes until to be obtained the desired structures. The characterization of these compounds was performed by means of infrared spectroscopic (FTIR) and nuclear magnetic resonance spectroscopic measurements (RMN H1). Beside the preparation and the characterization of the organic compounds aiming to the obtation of electroluminescents polymers, this text describes the preparation and the characterization of the poly(2-methoxy-5-bromo-pphenylenevinylene) (MB-PPV), a polymer which could present similar properties to those intended to the formed, prepared from the compounds described in the first phase of this work. This polymer was electrochemically prepared, and the electron transfer process that occurs during its formation was studied by means cyclic voltammetry and chronoamperometry measurements. During this synthesis it was obtained an insoluble fraction, in the form of powder, and a soluble fraction dissolved in chloroform and another one in methanol. For effect of comparison it was described the electrochemical preparation of the poly(2,5-dicyano-p-phenylenevinylene) (DCNPPV) and the PPV. These polymers were characterized by FTIR and UV-VISIBLE absorption spectroscopy and by measurements of fluorescence.